Deformation structures in central Nepal and their engineering geological significance (Journal of Nepal Geological Society, 1998)
Geological maps of the Helambu-Kathmandu area and Kathmandu-Hetauda area with their suitable cross-sections are presented. On the basis of the deformation history, the deformation structures recorded from the field study as well as from the air photo interpretations are classified as continuous and discontinuous deformation structures. All types of discontinuous deformation structures are considered as discontinuities. Discontinuities play decisive role in engineering geology breaking the continuity of the mechanical behaviour of the rockmass at different scales. On the basis of spacing, width, mineral fill and extent, the discontinuities are classified into seven orders. Such classification is essential and appropriate for rockmasses, which are heavily affected by intense tectonic deformation in the Himalaya, the Alps or corresponding orogens. The study area within central Nepal is having many engineering geological problems. Stability of the rock slopes and underground excavations are two major engineering geological problems to deal here with. Significance of the different order of discontinuities in the light of these engineering geological problems are discussed. Orientation of different order of discontinuities is an important parameter affecting blasting, span width, roof support and ground water flow and related problems in the proposed tunnels in the study area. Such structures are also important factor for the stability of the natural slopes and cut slopes.